The Perception Regarding the Urban Environment in Romanian Cities - Florica ŞTEFĂNESCU; Sergiu BĂLŢĂTESCU (Transylvanian Review of Administrative Sciences, 2013)
The present paper brings forth an analysis of the urban inhabitants’ perception regarding the quality of environmental factors. The research is based on a secondary analysis using data provided by the Flash Eurobarometer 277: Urban Audit Perception Survey. The main conclusion of this paper is centered on the fact that Romanian urban inhabitants give little attention to environmental factors, their priorities targeting other areas like work and health connected issues. A greater amount of attention to environmental factors is given by the more educated population which is more aware of the environmental factors’ importance for their daily life. The practical conclusion of the study consists in the necessity to make the whole population aware of the environmental problems, in view of adopting an appropriate behavior and attitudes regarding urban surroundings. The public administration has to play a key role in this respect, thus the paper tries to underline the possible outcomes that this situation can have on the decisions made by local authorities.